Fabrication Of Cooling Jig Using Electro Discharge Machining (Edm) - Senin, Azman (2002)
For a high quantity production system such as PROTON, maintenance of equipments and related facilities at the production line is one of the critical factors to ensure the success of Just In Time system (JIT) and Synchronised System. A higher breakdown of equipments will affect the delivery to next processes and uncertain level of quality. This project focused on body assembly process where this process is the second process in Proton cars manufacturing process. It features a mix of a variety type of welding assembly jig, welding equipments, material handling equipments and robots. A demand arises when the spare part of existing welding assembly jig - Cooling Jig is not available and extensive maintenance is required in maintaining the Cooling Jig. This project focus on re-modelled and fabrication of Cooling Jig. The fabrication process needs information on surface data instead of detail drawing. But, the information such as surface data is not available in Jig Making & Maintenance (JMM) section. The surface data is obtained thorough digitising process with coordinate measuring machine and produced the Cloud point data in a neutral data format (ASCII format). Then, Catia software was used to convert the file into DXF format. The Cooling Jig's surface was obtained first before NC data conversion can be generated. The fabrication of Cooling Jig is using EDM wire cut. Prior to machining, the Design of Experiment (DOE) was used as a method to obtain the optimum machining time and wire breakage without carrying numerous numbers of experiments at EDM Wire Cut machine - R290P, Agie Charmilles. As a result, the In-House fabrication process reduced almost 60 % fabrication cost if outsourced and successfully forged a reverse engineering flows for JMM section.